Facilitators and barriers to centre- and home-based exercise training in breast cancer patients - a swiss tertiary centre experience. (11th May 2022) - Schneider, C; Reimann, S; Schmid, J; Bernhard, J; Campbell, KL; Wilhelm, M; Eser, P
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Swiss Cancer Research Background: Exercise is an effective therapy for cancer patients to reduce fatigue and to improve health-related quality of life and physical function. Yet, cancer patients often do not meet physical activity guidelines. Purpose: To understand why recommendations are not met, we aimed at identifying facilitators and barriers to supervised, centre-based exercise within a cardio-oncologic rehabilitation (CORE) programme and to unsupervised, home-based exercise as well as strategies used to manage these barriers. Methods: Breast cancer patients who had completed a CORE programme at a Swiss tertiary centre were recruited. Semi-structured interviews were conducted with subsequent thematic analysis. Results: Of 37 eligible breast cancer patients, 19 patients (mean age 48.9±9.7 years) participated to our invitation. Facilitators for centre-based exercise were social support, committedness and provision of structured exercise. Barriers towards centre-based exercise included physical and environmental barriers, while psychological barriers were reported predominantly for home-based exercise. Strategies to manage barriers included the adaptation of training circumstances, behaviour change strategies and strategies to deal with side effects. Conclusions: Our results support the importance of providing CORE programmes and suggest that a special focus should be directed at the transition from supervised to self-organized exercise in order to enhance long-term exercise participation.